Azadirachta indica triterpenoids promote osteoblast differentiation and mineralization in vitro and in vivo - Kushwaha, Priyanka; Khedgikar, Vikram; Haldar, Saikat; Gautam, Jyoti; Mulani, Fayaj A.; Thulasiram, Hirekodathakallu V.; Trivedi, Ritu (Bioorganic & Medicinal Chemistry Letters, 2016)
Terpenoids were isolated using chromatographic purification through solvent purification technique and identified as Azadirone (1), Epoxyazadiradione (2) Azadiradione (3) Gedunin (4) Nimbin (5) Salannin (6) Azadirachtin A (7) and Azadirachtin B (8) from Azadirachta indica. Out of eight compounds, only three compounds had osteogenic activity and enhanced osteoblast proliferation, differentiation and mineralization in osteoblast cells. Active compounds stimulated osteogenic genes ALP, RunX-2 and OCN expressions in vitro, but Azadirachtin A had a maximum ability to stimulate osteoblast differentiation and mineralization compared to other two active compounds. For in vivo study, Azadirachtin A injected subcutaneously in pups, which enhanced osteogenic gene expressions and promoted bone formation rate significantly. Here, we conclude that active compounds of Azadirachta indica have osteogenic activity and Azadirachtin A has a beneficial effects on bone. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: ALP and mineralization assay; Balb/c mice pups; Calvarial osteoblast cells; Gene expressions